Social obligation in land ownership and it's management under Shari'ah - Mohamad, Nor Asiah; Sufian, Azlinor (2009)
Principles of land ownership in Islam are derived from Divine ;aw which evolved into a legal corpus developed by Muslim legal jurists. Those legal injuctions explicitly stated in the Qur'an were revealed to all of mankind and cover all aspects of human life. This paper aims to show that the legal concept of land ownership in Islam responsibility which manifests itself in its principles and social norms. This article discusses the elements of social obligations as reflected in the legal principles governing land ownership. Absolute land ownership is the sole right of Allah, while the Muslim community enjoys and executes limited private and public land rights, trespass liability, taxes regimes, neighborhood principles and environmental responsibility.